Protocol for quantifying porosity percentage in plant tissues - Restrepo García, Ana María (CGIAR Initiative on Accelerated Breeding, 2023)
There are different methodologies to determine the porosity in plants, like microscopical cross-sectioning, that involve cutting thin slices of the roots or stem and examine them under the microscope, to obtain information about the internal structure. This methodology implies a clear vision of the anatomical structure but normally is time consuming and labour-intensive due cutting of material (Visser & Bögemann, 2003). On the other hand, there are other methodologies to calculate the percentage of porosity by weighing plant material before and after de the air canals of the plant are filled with water, allowing a faster way to process samples, and reducing the amount of material examine under microscope (Visser & Bögemann, 2003). According to what was mentioned, this protocol describes the steps to obtain the percentage of porosity of stems and roots by weighing before and after the degassing the tissue, a simple methodology that requires little time, in order to be applied and reproducible in in upcoming trials.